Distribution of calanoid copepods across the mesoscale frontal zone of tropical-subtropical convergence off México. (November 2019) - Cruz-Hernández, Javier; Sánchez-Velasco, Laura; Beier, Emilio; Godínez, Victor M.; Barton, Eric D.
Abstract: The distribution of calanoid copepods was investigated in the convergence zone between the California Current Water and Transitional Tropical Water in June 2010 to understand how this zooplankton community responds to mesoscale environmental structure. Hydrographic conditions and zooplankton profiles were measured along two transects which crossed a mesoscale front and adjacent structures, visible in sea surface temperature and ocean color satellite images. The hydrographic structure showed strong temperature ( 2 °C) and oxygen (50 μ mol kg −1 ) gradients in the frontal zone ( 90 km) associated with a sinking of the thermocline and oxycline, from 30 m depth in the Transitional Tropical Water, to 90 m depth in the California Current Water. The front was marked by a salinity minimum (<34.3 g kg −1 ) that sank along the sloping thermocline. High chlorophyll- a concentrations associated with the thermocline were detected in the Transitional Tropical Water, where a cyclonic eddy was defined. These concentrations decreased as the thermocline depth increased. Multivariate analysis defined three calanoid copepod habitats related to the hydrographic structure. A habitat with the highest copepod concentration (24, 704 copepods 1000 m −3 ) was found on the tropical water side associated with a cyclonic eddy. Subeucalanus subtenuis and Centropages furcatus, indicator species, were concentrated between the thermocline ( 30 m depth) and the sea surface. On the subtropical water side, where the thermocline was deeper, a habitat with the lowest copepod concentration (3304 copepods 1000 m −3, an order of magnitude smaller), characterized by Euchaeta indica and Centropages elongates, was observed. As an unexpected result, the habitat located in the frontal zone, characterized by Scolecithrix bradyi and Heterorhabdus papilliger had low copepod concentration (4453 copepods . 1000 m -3 ). This low concetration could be due to the steep thermocline slope in the frontal zone, which could cause the thermocline depth to rapidly exceed the photic zone depth, and therefore affect the availability of food for calanoid copepods. It is concluded that the definition of the calanoid copepod habitats, was not only caused by the front itself, but by its interaction with other fine-scale mechanisms that generate oceanographic conditions leading to development of different food webs depending on the structure of water column.